“There is nothing that can prevent me from supporting her:” men’s perspectives on their involvement and support of women’s use of topical therapy for cervical precancer treatment in Kenya - Mungo, Chemtai; Adewumi, Konyin; Adoyo, Everlyn; Zulu, Graham; Goraya, Supreet Kaur; Ogollah, Cirillus; Omoto, Jackton; Ferrari, Renée M.; Rahangdale, Lisa (Frontiers in Oncology, 2024)
Purpose: Cervical cancer disproportionately impacts women in low-and middle-income countries (LMICs). The World Health Organization's 90/70/90 strategy aims to eliminate cervical cancer by 2030 by increasing HPV vaccination coverage, screening, and effectively treating cervical precancer, potentially preventing 62 million deaths in LMICs. LMICs, however, struggle with limited access to cervical precancer treatment, in part due to a lack of trained professionals and weak health systems. Effective nonsurgical, self-administered precancer therapies could bridge the treatment gap in LMICs and may be more scalable and cost-effective than provider-administered treatment. To inform feasibility studies in LMICs, data are needed on the role of male partners in influencing the acceptability and uptake of self-administered therapies, including their support of recommended abstinence and contraception guidelines associated with these therapies.Methods: Between November 2022 and April 2023, we conducted five focus group discussions (FGDs) with men aged 25 to 65 years in Kenya to explore their perspective and perceived support regarding their female partners using topical self-administered therapies for cervical precancer treatment. The FGDs were moderated by local qualitative research assistants and conducted in local languages, transcribed, coded, and analyzed using qualitative description.Results: Thirty-nine male participants meeting the eligibility criteria participated in five FGDs. The mean age of participants was 42.5 years. Most participants, 79.5%, had a female partner with a history of cervical precancer treatment, 5.1% did not, and 15.4% were unsure of their female partner's prior precancer treatment history. The study aimed to assess men's support of their female partners' use of topical therapies for treating cervical precancer. We find that male participants strongly express acceptance and willingness to support their wives or partners in using such therapies, if available. Reported supportive behavior included permitting the use of the therapies and support of maintaining abstinence during the recommended times. Additionally, participants desired male involvement in clinic and community-based education to facilitate widespread support. Self-applied topical treatments for cervical precancer could help meet the WHO's 2030 target of 90% treatment access in LMICs. We find that with adequate education, men express support of their partner's use of topical therapies, including adherence to abstinence and contraception guidelines.